Diverse Mechanisms of BRAF Inhibitor Resistance in Melanoma Identified in Clinical and Preclinical Studies - Luebker, Stephen A.; Koepsell, Scott A. (Frontiers in Oncology, 2019)
BRAF inhibitor therapy may provide profound initial tumor regression in metastatic melanoma with BRAF V600 mutations, but treatment resistance often leads to disease progression. A multi-center analysis of BRAF inhibitor resistant patient tissue samples detected genomic changes after disease progression including multiple secondary mutations in the MAPK/Erk signaling pathway, mutant BRAF copy number gains, and BRAF alternative splicing as the predominant putative mechanisms of resistance, but 41.7% of samples had no known resistance drivers. In vitro models of BRAF inhibitor resistance have been developed under a wide variety of experimental conditions to investigate unknown drivers of resistance. Several in vitro models developed genetic alterations observed in patient tissue, but others modulate the response to BRAF inhibitors through increased expression of receptor tyrosine kinases. Both secondary genetic alterations and expression changes in receptor tyrosine kinases may increase activation of MAPK/Erk signaling in the presence of BRAF inhibitors as well as activate PI3K/Akt signaling to support continued growth. Melanoma cells that develop resistance in vitro may have increased dependence on serine or glutamine metabolism and have increased cell motility and metastatic capacity. Future studies of BRAF inhibitor resistance in vitro would benefit from adhering to experimental parameters that reflect development of BRAF inhibitor resistance in patients through using multiple cell lines, fully characterizing the dosing strategy, and reporting the fold change in drug sensitivity.